META ANALISIS LATIHAN DRILL DALAM MENINGKATKAN KETEPATAN PUKULAN SMASH ATLET BULUTANGKIS - Muhammad Hasbi Ash Shiddieqy; adrizal, mohd; Sukendro, Sukendro (Journal Score, 2025)
The aim of this research is to re-analyze the use of the drill training method in improving the accuracy of badminton smash shots. The method used in this research is meta analysis. Research begins by formulating a research problem, exploring research results that are relevant for analysis. Data was collected by searching electronic journals via Google Scholar with the keywords "drill", "smash accuracy". From this search, 20 relevant articles were obtained. Based on the results of the analysis, the drill training method was able to increase the accuracy of smash shots from the lowest 2.50% to the highest 41.94% with an average of 10.93%.